2004
DOI: 10.1590/s0004-27302004000100019
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone and adrenergic signaling in the heart

Abstract: Thyroid hormone action has profound consequences for the heart, ranging from atrial fibrillation to hemodynamic collapse. It has long been known that the cardiovascular signs and symptoms seen in thyrotoxicosis resemble those seen in states of catecholamine excess. However, measured concentrations of serum catecholamines in patients with thyrotoxicosis are typically normal or even low, suggesting an increase in the adrenergic responsiveness of the thyrotoxic heart. In spite of several decades of work, the ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
17
0
2
Order By: Relevance
“…Epidemiological studies have reported a significant correlation between low birth weight and the later development of adult diseases associated with higher systolic blood pressure (Barker, 2004). Additionally, we previously showed that leptin‐treated rats had higher triiodothyronine and thyroxine levels with a lower serum thyrotropin concentration (Teixeira et al 2003), and it is well established that thyroid hormones increase β 1 ‐adrenergic receptor expression in the heart (Kim et al 2004). Thus, these changes in cardiovascular parameters could be due to several factors including hyperleptinaemia, increased function of the adrenal medulla or raised levels of thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have reported a significant correlation between low birth weight and the later development of adult diseases associated with higher systolic blood pressure (Barker, 2004). Additionally, we previously showed that leptin‐treated rats had higher triiodothyronine and thyroxine levels with a lower serum thyrotropin concentration (Teixeira et al 2003), and it is well established that thyroid hormones increase β 1 ‐adrenergic receptor expression in the heart (Kim et al 2004). Thus, these changes in cardiovascular parameters could be due to several factors including hyperleptinaemia, increased function of the adrenal medulla or raised levels of thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Defending core temperature during cold exposure depends on a series of adaptive mechanisms mostly initiated by the SNS. However, because of modifications in the adrenergic signal transduction system, hypothyroid animals respond much less to catecholamines, and the opposite is observed in thyrotoxic animals (622)(623)(624). Thus, hypothyroid rodents exhibit profound hypothermia and succumb in a matter of hours when exposed to cold (4°C-5°C) (625,626).…”
Section: And Recommendation 56amentioning
confidence: 99%
“…They also have direct positive inotropic and chronotropic effects. 15,16 However, adrenergic hyperactivity suppresses thyroid function and leads to low T3. 7,10,11 Suppression of thyroid function decreases cardiac adrenergic receptors and reduces the response to catecholamine.…”
Section: Discussionmentioning
confidence: 99%